FACTORS AFFECTING SUBJECTIVE WELL BEING OF TRANSFEMORAL PROSTHESIS USER IN INDONESIA - Rachmat, Nur; Fanani , Mohammad; Darsono, Darsono; Suwarto, Suwarto (Advances in Social Sciences Research Journal, 2020)
Study Design: This research is Quantitative Research using analytic observational with a cross-sectional approach. Background: Amputation hurts patients physically, psychologically and socially. Permanent physical disability due to amputation affects the thought, feeling and behavior of the patient, because patient will have the negative feeling on body image that can cause a feeling that he is not useful, worry about losing his job, pessimistic about the future and limit social relationships with self-withdrawal, so that patient will experience depression. Objectives: This research is to determine the factor affecting the subjective well being of transfemoral prosthesis users in Indonesia. Methods: The sample in this study was 110 users of the transfemoral prosthesis with a simple random sampling technique. The Data collection technique is using questionnaires and documentation. It was used Structural Equation Modeling (SEM) to analyze the data. Results: The result of this study had a statistically significant effect between motivation (p = 0.031), self-efficacy (p = 0.030), religiosity (p = 0.020), social support (p = 0.027), and optimism (p = 0.033) toward subjective well being. Conclusions: motivation, self-efficacy, religiosity, social support and optimism are the factors affecting the subjective well being of transfemoral prosthesis users in Indonesia. Clinical Relevance: Patient who had undergone amputation will have an effect on their subjective well being. It is important to know the factor affecting subjective well being of above knee amputation that use prosthesis. The factors are motivation, self-efficacy, religiosity, social support and optimism.